Analiza cykli ubezpieczeniowych w ubezpieczeniach satelitarnych - Manikowski, Piotr; Weiss, Mary, A. (Analysis of Underwriting Cycles in Satellite Insurance, 2008)
The underwriting cycle refers to a repeating series of phases that insurance markets go through. The sequence of "hard" and "soft" markets may be observed in prices, profitability, and supply (capacity) for insurance. The typical description of the cycle includes four phases: recession, crisis, revival, and boom. In the satellite insurance literature, volatility and cyclicality of results are emphasized. And it appears that the market does go through the four phases of the underwriting cycle. The evidence presented above is based on casual market observations, however, not rigorous empirical/statistical analysis. Moreover, it is unknown which specific market parameters (e.g., capacity, rates, underwriting results) are subject to cyclical fluctuations. The purpose of this paper is to provide a rigorous analysis of the satellite insurance market to determine whether it is cyclical in nature. In addition, if a cycle is found, we also investigate the cycle length. To obtain the required parameters for testing for the existence of the underwriting cycle and to estimate cycle periods models proposed by Venezian (1985) were used.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 237-242